One-Pot Synthesis of Quinoxaline N-Oxides via Radical-Mediated Cyclization of Ketene N,S-Acetals - Kumar, Ganesh; Ray, Subhasish; Shukla, Gaurav; Singh, Maya Shankar (Synthesis, 2023)
A facile and efficient one-pot synthesis of bench-stable quinoxaline N-oxides has been realized using α-oxoketene N,S-acetals and tert-butyl nitrite (TBN) in open air via cascade annulation. The double functionalization of N,S-acetals proceeds through an unanticipated (Csp2)–H nitrosation by NO radical (generated in situ by TBN) and subsequent intramolecular N-arylation leading to quinoxaline, which undergoes oxidation to quinoxaline N-oxides harboring three variegated substituents on their framework. Notably, two new C–N bonds are formed with the same N-oxide nitrogen. This protocol features short reaction time, good functional group tolerance and mild conditions, and does not require the use of either catalyst or external additive.
Keywords: ketene N,S-acetals; tert-butyl nitrite (TBN); radical coupling; quinoxaline N-oxides